High‐Quality, Ligands‐Free, Mixed‐Halide Perovskite Nanocrystals Inks for Optoelectronic Applications. Issue 8 (19th December 2016) - Lamberti, Francesco; Litti, Lucio; De Bastiani, Michele; Sorrentino, Roberto; Gandini, Marina; Meneghetti, Moreno; Petrozza, Annamaria
Abstract : The use of laser‐ablation‐assisted solution synthesis of ligand‐free perovskite semiconductor inks is demonstrated. The thin films exhibit no hysteresis under polarization and monotonic tunability of the semiconductor band/gap.